2015
DOI: 10.1007/s00395-015-0518-1
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 attenuates adverse cardiac remodelling in streptozocin-induced diabetes via specific actions on infiltrating macrophages

Abstract: In addition to its' established metabolic and cardioprotective effects, glucagon-like peptide-1 (GLP-1) reduces post-infarction heart failure via preferential actions on the extracellular matrix (ECM). Here, we investigated whether the GLP-1 mimetic, exendin-4, modulates cardiac remodelling in experimental diabetes by specifically targeting inflammatory/ECM pathways, which are characteristically dysregulated in this setting. Adult mice were subjected to streptozotocin (STZ) diabetes and infused with exendin-4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 49 publications
6
76
0
Order By: Relevance
“…Some studies have attributed the benefits of Ex‐4 on DCM to its effects on infiltrating macrophages, cardiac microvascular injury, and mitochondrial dysfunction (Tate et al., 2016; Wang et al., 2013; Wassef et al., 2017). However, the present study mainly focused on the effects of GLP‐1 on lipid regulation because, along with hyperglycemia, lipid accumulation and toxicity play key roles in DCM (Kusminski et al., 2009; Yang et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have attributed the benefits of Ex‐4 on DCM to its effects on infiltrating macrophages, cardiac microvascular injury, and mitochondrial dysfunction (Tate et al., 2016; Wang et al., 2013; Wassef et al., 2017). However, the present study mainly focused on the effects of GLP‐1 on lipid regulation because, along with hyperglycemia, lipid accumulation and toxicity play key roles in DCM (Kusminski et al., 2009; Yang et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…GLP‐1R agonists and DPP‐4 inhibitors have beneficial effects on the cardiovascular system (Ban et al., 2008; Noyan‐Ashraf et al., 2009; Timmers et al., 2009). Previous studies have shown that GLP‐1 and its analogs protected the heart against ischemia‐reperfusion injury and diabetes mellitus (Tate, Robinson, Green, McDermott & Grieve, 2016; Wang et al., 2013). They also protected isolated CMs from oxidative damage (Chang et al., 2013) and high‐glucose stress (Younce, Burmeister & Ayala, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The right jugular vein was visualized and cannulated for intravenous drug infusions. See Methods and Materials Section from DelloStritto et al, for complete description [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Mice were infused with capsaicin (1–100 μg/kg), 4-HNE (4 mg/kg over 10 min), and non-targeted contrast. For complete description of methods, see Guarini et al [4] and DelloStritto et al [25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation